Financial Self-Efficacy and Disposition Effect in Investors: The Mediating Role of Versatile Cognitive Style - Tang, Song; Huang, Shimin; Zhu, Jia; Huang, Rui; Tang, Zilong; Hu, Jianping (Frontiers in Psychology, 2019)
The disposition effect refers to the tendency of investors to sell winners too early and hold on to losers too long, which is one of the most documented and robust decision biases. However, few studies have looked beyond demographic and social factors on the disposition effect. The current study investigated the association between financial self-efficacy (one’s belief about their personal capability in ultimate financial goals achieving), versatile cognitive style (an individual’s capability in deploying the experiential or rational mode in ways that are contextually appropriate), and the disposition effect. A total of 285 employees from finance-related business completed anonymous questionnaires regarding financial self-efficacy, rational-experiential inventory, and the disposition effect. Our findings revealed that financial self-efficacy was significantly and positively associated with versatile cognitive style and the disposition effect. Further, versatile cognitive style partially mediated the relationship between financial self-efficacy and the disposition effect. Our findings provide valuable guidance for individual investors to make financial decisions based on their characteristics.